1972
DOI: 10.1172/jci106868
|View full text |Cite
|
Sign up to set email alerts
|

Phenobarbital-Induced Alterations in Vitamin D Metabolism

Abstract: A B S T R A C T The metabolic fate of intravenously injected vitamin D3-1,2-'H (Ds-'H) was studied in two normal individuals on chronic phenobarbital therapy. Silicic acid column chromatography of lipid-soluble plasma extracts obtained serially for 96 hr after D3-'H injection demonstrated a decreased plasma Ds-'H halflife and increased conversion to more polar metabolites. The polar metabolites formed included several with chromatographic mobility similar to known biologically inactive vitamin D metabolites an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
85
2
3

Year Published

1973
1973
2007
2007

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 290 publications
(95 citation statements)
references
References 21 publications
5
85
2
3
Order By: Relevance
“…A lack of vitamin D is well known to lead to rickets and / or osteomalacia in animals (11). Antiepileptic agents induced liver microsomal P-450-containing oxidases, which subsequently leads to an increased rate of catabolism of vitamin D and its derivatives to inactive metabolites (12,13). However, the present biochemical data indicated that the serum 25OHD levels are not decreased compared with that of the normal group.…”
Section: Discussioncontrasting
confidence: 70%
“…A lack of vitamin D is well known to lead to rickets and / or osteomalacia in animals (11). Antiepileptic agents induced liver microsomal P-450-containing oxidases, which subsequently leads to an increased rate of catabolism of vitamin D and its derivatives to inactive metabolites (12,13). However, the present biochemical data indicated that the serum 25OHD levels are not decreased compared with that of the normal group.…”
Section: Discussioncontrasting
confidence: 70%
“…This drug is known to impair bone metabolism through several mechanisms. First, it stimulates hepatic mixed function oxidase activity, accelerating the breakdown of vitamin D metabolites (11). In addition, both phenobarbital and phenytoin interfere with active transport of calcium in the small intestine (21).…”
Section: Discussionmentioning
confidence: 99%
“…Classical AEDs associated with abnormal bone and mineral metabolism are those that induce cytochrome P450 enzymes, such as carbamazepine, phenytoin and phenobarbital (9,10). These drugs induce hepatic microsomal enzymes that increase catabolism of 25OHD (11). Other drugs that are not enzyme inducers, such as sodium valproate, may exert indirect effects on bone metabolism by altering renal function (12).…”
mentioning
confidence: 99%
“…Chronic phenobarbital ingestion has been shown to increase the rate of disappearance of 3 H-vitamin D 3 from plasma in humans (15)(16)(17). Liver microsomes from phenobarbital-treated animals are capable of increasing hydroxylation of steroid hormones (7,20,24) and of converting 3 H-labeled vitamin D 3 and 3 H-labeled 25-OH-D 3 rapidly to more polar metabolites in vitro [15].…”
Section: Introductionmentioning
confidence: 99%